Arctic Corridors and Northern Voices: Governing marine transportation in the Canadian Arctic Kapiangaqiyuaq (Paulatuk, Inuvialuit Settlement Region, Northwest Territories community report) - Carter, Natalie Ann; Dawson, Jackie; Parker, Colleen; Cary, Julia; Gordon, Holly; Kochanowicz, Zuzanna; Weber, Melissa (Université d'Ottawa | University of Ottawa, 2018)
Ship traffic in the Canadian Arctic nearly tripled between 1990 and 2015. The Government of Canada is developing a network of low-impact marine transportation corridors in the Arctic that encourages marine transportation traffic to use routes that pose less risk and minimize the impact on communities and the environment. The Low Impact Shipping Corridors will be a framework to guide future federal investments to support marine navigation safety in the North, including improved charting and increased hydrography, in partnership with Northerners. The corridors initiative is co-led by the Canadian Coast Guard, Transport Canada, and Canadian Hydrographic Service. Key considerations in the current prioritization of the Low Impact Shipping Corridors include identification of Inuit and Northerners’ perspectives on 1) the potential impact of marine vessels on marine areas used for cultural and livelihood activities, and on community members; and 2) potential management strategies for the corridors. This report documents Paulatuk community members’ knowledge and extensive year-round use of important marine areas (ecological, socio-cultural, archaeological, and travel routes), the potential impacts of shipping on those areas and on community members, and recommendations for management of the Low Impact Shipping Corridors. The Beaufort Sea Beluga Management Plan, the Paulatuk Char Conservation Plan and the Paulatuk Community Conservation Plan should be referenced to supplement the findings of this report.
Keywords: Low impact shipping corridors; Inuit perspectives; Marine transportation governance; Culturally significant marine areas; Arctic shipping impacts